ORGANIZING THE ACCOUNT OF PROFIT TAX INDICATORS ON THE BASIS OF THE REQUIREMENTS OF INTERNATIONAL STANDARDS - Yuliyev Sanjar Rajabovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. In the article, the factors affecting the profit tax base in the conditions of international integration of accounting, the issues of the correct formation of the tax base are covered